The Effect of Lactation Massage With Smooth Breast Milk on Postpartum Mothers in Desa Lawa-Lawa Ulu Idanotae, Kec. Ulu Idanotae, Kab. South Nias - Nurhamida Fithri; Herlina Simanjuntak; Faradita Wahyuni (Pena Cendekia Insani, 2022)
Objectives: Breast milk is the only food and drink a baby needs until he is 6 months old, which can help absorb nutrients. Exclusive breastfeeding for up to 6 months seems still difficult to implement so that the target of the community nutrition improvement program to increase exclusive breastfeeding is not achieved. One of the efforts to increase breastfeeding with smooth breast milk is through lactation massage, which is a massage technique to clean the ducts and stimulate milk production to be smoother. The purpose of this study was to identify the effect of lactation massage on breastfeeding in postpartum mothers in Lawa-Lawa Village, Luo Idanotae. Method: The type of research used is quantitative with an experimental research design (quasi quasi). The sample in this study were all mothers who breastfeed from o-6 weeks of the postpartum period as many as 30 respondents using the Totaling Sampling method. The research instrument used was an observation sheet with closed observations. Data analysis used bivariate analysis through the Wilcoxon Rank Rest statistical test. Result: The results of the study showed that after the lactation massage test the p value was 15.00, so it could be seen that there was a difference in the smoothness of breast milk before and after lactation massage, besides the p value was 0.000 (p<0.05), which means that there was an effect of lactation massage. with significant breast milk fluency between before and after massage. Conclusion: This study shows that there is a significant effect on the smoothness of breastfeeding after massage for postpartum mothers in Lawa-Lawa Luo Idanotae Village, Ulu Idanotae District, South Nias Regency in 2021